2017
DOI: 10.3765/plsa.v2i0.4059
|View full text |Cite
|
Sign up to set email alerts
|

A pilot acoustic study of Modern Persian vowels in colloquial speech

Abstract: Abstract. While the current literature on Modern Persian (MP) 1 shows heightened interest in its vowel inventory, a cogent synchronic account of Modern Persian vowels (MPV) has yet to be presented. Previous phonological descriptions of MPV presuppose a pairing system based on a historical length distinction that is still reflected in MP orthography: /i:, e/, /u:, o/, /ɒ:, ae/. A synchronic phonological analysis of MPV must be based on phonetic measurements; however, existing acoustic studies examine only form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…It is intriguing that the vowel pattern in Cluster 1 with maximal separation of /i u/ and fronting of /a/ is very similar to the pattern of the Modern Persian vowel system (Figure 3G), in which the non-low short vowels are lowered to mid vowels /e/ and /o/ and the low vowels have a [±back] contrast. Acoustic studies of Persian vowels (Aronow et al 2017, Mokari et al 2017, Hemmatnia et al 2019) report mean F1 values of Persian short vowels (/æ/: M = 800 Hz; /e/: M = 500 Hz; /o/: M = 550 Hz) that are very close to mean F1 values of short vowels found in the current study (/a/: M = 698 Hz; /i/: M = 535 Hz; /u/: M = 550 Hz). Diagrams of vowel spaces for individual speakers of Persian (Mokari et al 2017: 13) look very similar to diagrams for speakers of Qatari Arabic in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is intriguing that the vowel pattern in Cluster 1 with maximal separation of /i u/ and fronting of /a/ is very similar to the pattern of the Modern Persian vowel system (Figure 3G), in which the non-low short vowels are lowered to mid vowels /e/ and /o/ and the low vowels have a [±back] contrast. Acoustic studies of Persian vowels (Aronow et al 2017, Mokari et al 2017, Hemmatnia et al 2019) report mean F1 values of Persian short vowels (/æ/: M = 800 Hz; /e/: M = 500 Hz; /o/: M = 550 Hz) that are very close to mean F1 values of short vowels found in the current study (/a/: M = 698 Hz; /i/: M = 535 Hz; /u/: M = 550 Hz). Diagrams of vowel spaces for individual speakers of Persian (Mokari et al 2017: 13) look very similar to diagrams for speakers of Qatari Arabic in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Other languages with tense/lax distinction in vowels, e.g. English or Persian, reveal smaller durational differences between the two vowels subsets, with the ratios between 0.72 and 0.82 (Peterson & Lehiste 1960, Hillenbrand et al 1995 for English; Aronow et al 2017, Mokari et al 2017, Hemmatnia et al 2019 for Persian). The differences in vowel duration might explain why vowel duration is a more salient feature in Arabic, but vowel quality is more salient in English or Persian.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 shows 23 consonants in Modern Colloquial Persian, which are set on the basis of place and manner of articulation (Alqahtani, 2020; Hosseini, 2014; Mahootian, 1997; Windfuhr, 1987). Vowels in Modern Colloquial Persian are divided into three short vowels, /e, æ, o/, of the [–long] feature, and three long counterparts, /i, u, ɑ/, of the [+long] feature, as shown in Table 2 (Aronow et al, 2017; Kambuziya et al, 2017; Miller, 2013).…”
Section: The Phonology Of Modern Colloquial Persianmentioning
confidence: 99%
“…Several studies have focused on the acoustic features of vowels -first and second formants -in Farsi (Ansarin 2004;Aronow et al 2017;Esfandiari et al 2015;Ghaffarvand Mokari et al 2017;Mohammadi et al 2011). Ghaffarvand Mokari et al (2017) reported the F0, F1, F2, and F3 and the duration of the Farsi vowels of 28 male and 25 female Farsi monolinguals with Tehrani dialect.…”
Section: Acoustics Of Farsi Vowelsmentioning
confidence: 99%